KEBIJAKAN PENINGKATAN KUALITAS PENDIDIKAN MENENGAH DALAM RANGKA OTONOMI DAERAH DI KOTA MAKASSAR - Mariah Mariah (AkMen JURNAL ILMIAH, 2011)
Along with regional autonomy with the principle of decentralization, improvement of the quality of education requires the participation and empowerment of all components of education as a system. Approach to improving the quality of education in accordance with the above paradigm dn idea is the concept of School Based Management or school-based management (SBM) Quality education can be seen from two things, namely ppendidikan refers to the process and outcomes of education. The process of quality education if the entire educational component involved in the educational process itself. The factors in the educational process are the various inputs, teaching materials, methodology, and administrative support for infrastructure and hail ppendidikan which refers to the achievements reached by the school at a certain time.